Antarctic ozone: Meteoric control of HNO 3 - Prather, Michael J; Rodriguez, Jose M (Geophysical Research Letters, 1988)
Atmospheric circulation leads to an accumulation of debris from meteors in the Antarctic stratosphere at the beginning of austral spring. The major component of meteoric material is alkaline, comprised predominantly of the oxides of magnesium and iron. These metals may neutralize the natural acidity of stratospheric aerosols, remove nitric acid from the gas phase, and bond it as metal nitrates in the aerosol phase. Removal of nitric acid vapor has been previously shown to be a critical link in the photochemical depletion of ozone in the Antarctic spring, by allowing for increased catalytic loss from chlorine and bromine.